2020
DOI: 10.31883/pjfns/120183
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Physicochemical, Mechanical, and Sensory Properties of Bioplastics from Phosphate Acetylated Arenga Starches

Abstract: an alternative to plastic packaging due to their environmental friendliness and easy degradation. Therefore, there is an urgent need for bioplastics due to the rapid increase in the pace of plastic production and air pollution causing several health risks because of their toxic nature [Jain & Tiwari, 2015]. Bioplastics are, however, very suitable alternatives to improve the quality of life and maintain a pollution-free planet [Keziah et al., 2018]. It has been discovered that bioplastics made from native starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…The WVTR of the biofilms was determined based on the method designed by Rahim et al. (2020) as follows: the chamber (jar) with a diameter of 10 cm and a height of 12 cm was first adjusted to relative humidity of 75% by adding a solution of 50% NaCl (w/v).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WVTR of the biofilms was determined based on the method designed by Rahim et al. (2020) as follows: the chamber (jar) with a diameter of 10 cm and a height of 12 cm was first adjusted to relative humidity of 75% by adding a solution of 50% NaCl (w/v).…”
Section: Methodsmentioning
confidence: 99%
“…The WVTR of the biofilms was determined based on the method designed by Rahim et al (2020) as follows: the chamber (jar) with a diameter of 10 cm and a height of 12 cm was first adjusted to relative humidity of 75% by adding a solution of 50% NaCl (w/v). Then an acrylic cup with a diameter of 3 cm and height of 1.6 cm was filled with 6 g silica gel, covered with the biofilm of size 6 cm  8 cm and placed in the moisturized chamber.…”
Section: Water Vapor Transmission Rate (Wvtr)mentioning
confidence: 99%
“…After being homogeneous, 5 mL of sorbitol was added and stirred for 2 minutes while maintaining the suspension temperature at 60°C. The suspension was molded in a glass mold, allowed to stand at room temperature for 2 hours and then in an oven at 50°C for 24 hours [19].…”
Section: The Process Of Making Glass Bioplasticsmentioning
confidence: 99%
“…So, it is necessary to solve problems that can reduce the use of plastic cups, namely by formulating materials that can decompose naturally as materials for glass bioplastics. Bioplastic is an alternative to plastic packaging that can be made from natural materials that can be widely used because it is environmentally friendly and easily degraded [6]. One of the characteristics of bioplastics or plastics is their resistance to water.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have been involved in search of alternatives to plastic or better to say biodegradable plastics. It has been concluded that native arenga starch (NAS) obtained from A. pinnata can be utilized to produce bioplastics (Rahim et al, 2020). However, it has also been concluded that bioplastics manufactured from NAS have poor mechanical, physicochemical, functional, and sensory properties.…”
Section: Industrial Usesmentioning
confidence: 99%